2020
DOI: 10.1103/physrevd.101.071101
|View full text |Cite
|
Sign up to set email alerts
|

Improved limits on a hypothetical X(16.7) boson and a dark photon decaying into e+e pairs

Abstract: The improved results on a direct search for a new X(16.7 MeV) boson that could explain the anomalous excess of e + e − pairs observed in the decays of the excited 8 Be * nucleus ("Berillium anomaly") are reported. The X boson could be produced in the bremsstrahlung reaction e − Z → e − ZX by a high energy beam of electrons incident on the active target in the NA64 experiment at the CERN SPS and observed through its subsequent decay into e + e − pair. No evidence for such decays was found from the combined anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
118
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 93 publications
(108 reference statements)
1
118
0
Order By: Relevance
“…The recent inclusive experiment of the NA64 Collaboration [12][13][14] of finding no "dark" soft photon excesses needs to reconcile with the earlier finding of anomalous soft photon excesses in high energy hadron-p, pp, and e + e − collisions [23][24][25][26][27][28][29][30][31]. In the detection of anomalous soft photons in the DELPHI Collaboration [31], the photon detection is carried out by studying the electron and positron tracks in a TPC, while in the NA64 experiment, the produced soft photon needs to penetrate a calorimeter and is detected downstream in a separate calorimeter.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent inclusive experiment of the NA64 Collaboration [12][13][14] of finding no "dark" soft photon excesses needs to reconcile with the earlier finding of anomalous soft photon excesses in high energy hadron-p, pp, and e + e − collisions [23][24][25][26][27][28][29][30][31]. In the detection of anomalous soft photons in the DELPHI Collaboration [31], the photon detection is carried out by studying the electron and positron tracks in a TPC, while in the NA64 experiment, the produced soft photon needs to penetrate a calorimeter and is detected downstream in a separate calorimeter.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Recent observation [1] of a light, neutral boson decaying into an e + e − pair with a mass of about 17 MeV, in the decay of the I(J π ) = 0(1 + ) state of 8 Be at Atomki, has generated a great deal of interest [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Supporting evidence for this hypothetical X17 particle has been reported recently in the decay of the excited I(J π ) = 0(0 − ) state of 4 He [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the nucleus level, the decay is mediated by the operator O ð1Þ 3S in Eq. (29), which leads to the S-wave decay amplitude…”
Section: Axial Vector Xmentioning
confidence: 99%
“…A follow-up study from nuclear theory was also shown to disfavor a nuclear form factor as an explanation [27]. Follow-up measurements of the nuclear transitions have not been reported by other groups, but other experimental collaborations have provided new constraints on X boson couplings to electrons that exclude part of the viable parameter space in some models [28,29].…”
Section: Introductionmentioning
confidence: 97%